Planned cesarean section versus planned vaginal delivery: comparison of lower urinary tract symptoms - Ekström, Åsa; Altman, Daniel; Wiklund, Ingela; Larsson, Christina; Andolf, Ellika (INTERNATIONAL UROGYNECOLOGY JOURNAL, 2008)
We compared the prevalence and risk of lower urinary tract symptoms in healthy primiparous women in relation to vaginal birth or elective cesarean section 9 months after delivery. We performed a prospective controlled cohort study including 220 women delivered by elective cesarean section and 215 by vaginal birth. All subjects received an identical questionnaire on lower urinary tract symptoms in late pregnancy, at 3 and 9 months postpartum. Two hundred twenty subjects underwent elective cesarean section, and 215 subjects underwent vaginal delivery. After childbirth, the 3-month questionnaire was completed by 389/435 subjects (89%) and the 9-month questionnaire by 376/435 subjects (86%). In the vaginal delivery cohort, all lower urinary tract symptoms increased significantly at 9 months follow-up. When compared to cesarean section, the prevalence of stress urinary incontinence (SUI) after vaginal delivery was significantly increased both at 3 ( p < 0.001) and 9 months ( p = 0.001) follow-up. In a multivariable risk model, vaginal delivery was the only obstetrical predictor for SUI [relative risk (RR) 8.9, 95% confidence interval (CI) 1.9–42] and for urinary urgency (RR 7.3 95% CI 1.7–32) at 9 months follow-up. A history of SUI before pregnancy (OR 5.2, 95% CI 1.5–19) and at 3 months follow-up (OR 3.9, 95% CI 1.7–8.5) were independent predictors for SUI at 9 months follow-up. Vaginal delivery is associated with an increased risk for lower urinary tract symptoms 9 months after childbirth when compared to elective cesarean section.